An air-ground cooperative scheduling model considering traffic environment and helicopter performance. (August 2021) - Zhang, Ming; Li, Songrui; Li, Boquan
Highlights: A two‐stage four‐level scheduling network structure was established. The repair time and cost of the damaged road network were added into the model. Different helicopter performances were distributed under air scheduling. The A* algorithm was designed to plan the shortest route under air scheduling. The model shortened rescue time and cost compared with previous studies. Abstract: Air-ground cooperative rescue is restricted by terrain, weather, and helicopter performance. The rescue is also affected by the damage in road segments, which will then affect the emergency decisions, such as allocation of materials, helicopter scheduling, and vehicle scheduling in air-ground combined transportation. This study aims to determine the optimization scheme for emergency materials scheduling and transport of the wounded under a low-altitude operating environment and differences in helicopter performance. First, the air-ground cooperative scheduling network was presented. The effects of terrain and weather in the disaster-stricken area, operating environment, and constraints for carrying tools (helicopters and ground vehicles) involved in the emergency scheduling problem were also studied. Then, an air-ground cooperative emergency scheduling model that considered the differences in helicopter performance was established, and the distribution path of materials and the wounded, distribution quantity of emergency materials and transportation modes adopted by different paths were solved and determined through the designed algorithm. The improved model shortened the rescue time by 7.51% and lowered the rescue cost by 4.18% compared with models from previous studies. The results suggest this method can save more time and financial resources in terms of the air-ground cooperative scheduling problem. This study also provides an effective scientific basis for air-ground cooperative rescue work.